Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41436-020-00988-9
|View full text |Cite
|
Sign up to set email alerts
|

NEXMIF encephalopathy: an X-linked disorder with male and female phenotypic patterns

Abstract: R628* (x 5) R322* (x 4) K1396Rfs*3 C146* G681Vfs*11 K734Sfs*24 R481*(x 3) G1018Dfs*2 R528Efs*4 R218* (x 3) Q141Rfs*7 L209Pfs*3 R313* N573Sfs*11 S1157* S1200Ifs*5 (x3) R62Efs*22

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 39 publications
2
47
0
1
Order By: Relevance
“…One year later, Myers et al reported two other sisters diagnosed with MAE with a point mutation at NEXMIF (p.Arg322*) in their search of parental gonadal mosaicism in apparently de novo epileptic encephalopathies [ 41 ]. These two cases and their clinical features have recently been reviewed by Stamberger et al (2021) [ 42 ]. Analyzing the phenotype of 87 patients with NEXMIF -related encephalopathy, 10 females were diagnosed with EMA, 2 of them with an earlier onset (one year or younger), and 5 more cases (2 males and 3 females) presented a combination of EMA and MAE syndromes, including the case reported by Myers et al (2018)) ( Table 2 ) [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One year later, Myers et al reported two other sisters diagnosed with MAE with a point mutation at NEXMIF (p.Arg322*) in their search of parental gonadal mosaicism in apparently de novo epileptic encephalopathies [ 41 ]. These two cases and their clinical features have recently been reviewed by Stamberger et al (2021) [ 42 ]. Analyzing the phenotype of 87 patients with NEXMIF -related encephalopathy, 10 females were diagnosed with EMA, 2 of them with an earlier onset (one year or younger), and 5 more cases (2 males and 3 females) presented a combination of EMA and MAE syndromes, including the case reported by Myers et al (2018)) ( Table 2 ) [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…These two cases and their clinical features have recently been reviewed by Stamberger et al (2021) [ 42 ]. Analyzing the phenotype of 87 patients with NEXMIF -related encephalopathy, 10 females were diagnosed with EMA, 2 of them with an earlier onset (one year or younger), and 5 more cases (2 males and 3 females) presented a combination of EMA and MAE syndromes, including the case reported by Myers et al (2018)) ( Table 2 ) [ 42 ]. According to Stamberger et al, there was no correlation between phenotype and XCI status in their series, based on 1) the comparison of females with skewed and random XCI and 2) the families with sisters each presenting skewed and random XCI (families F4 and F7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, affected females have been described ( 10 14 ) and recently a large multicentric study outlined the epilepsy phenotype of affected females ( 15 ) which is consistent with a generalized DEE characterized by myoclonic–atonic epilepsy overlapping with eyelid myoclonia with absence. Notably a considerable proportion of affected females present prolonged seizures characterized by absence status with eyelid myoclonia ( 15 , 16 ). We report a female patient with a de novo NEXMIF pathogenic variant and recurrent prolonged episodes of absence status with eyelid myoclonia.…”
Section: Introductionmentioning
confidence: 87%
“…Pathogenic NEXMIF variants were first identified in males with non-syndromic X-linked ID with poor or absent speech, subtle dysmorphic features, and sometimes epilepsy (8,9). Subsequently, affected females have been described (10)(11)(12)(13)(14) and recently a large multicentric study outlined the epilepsy phenotype of affected females (15) which is consistent with a generalized DEE characterized by myoclonic-atonic epilepsy overlapping with eyelid myoclonia with absence. Notably a considerable proportion of affected females present prolonged seizures characterized by absence status with eyelid myoclonia (15,16).…”
Section: Introductionmentioning
confidence: 93%